Citrullinated glucose-regulated protein 78 is a candidate target for melanoma immunotherapy - Brentville, Victoria Anne; Symonds, Peter; Chua, JiaXin; Skinner, Anne; Daniels, Ian; Cook, Katherine Wendy; Koncarevic, Sasa; Martinez-Pinna, Roxana; Shah, Sabaria; Choudhury, Ruhul Hasan; Vaghela, Poonam; Weston, Daisy; et al. (Frontiers in Immunology, 2022)
Post translational modification of proteins plays a significant role in immune recognition. In particular the modification of arginine to citrulline which is mediated by PAD enzymes is increased during cellular stress (autophagy) which permits the presentation of modified epitopes upon MHC class II molecules for recognition by CD4 T cells. Citrullination also occurs in tumour cells as a result of continuous environmental stresses and increased autophagy. We have shown in animal models the efficient stimulation of citrullinated epitope specific CD4 T cells resulting in dramatic elimination/regression of tumours. The ER chaperone glucose-regulated protein 78 (GRP78) is known to also be required for stress-induced autophagy and is directly linked to autophagosome formation. GRP78 is known to be highly expressed by many tumour types. In this study we investigate the potential of targeting citrullinated GRP78 for cancer therapy. We select five peptides and show the identification CD4 T cell responses to one citrullinated GRP78 epitope that are restricted through HLA DP*0401 and HLA-DR*0101 alleles. This peptide is detected by mass spectrometry in B16 melanoma grown in vivo and citrulline specific CD4 responses to two peptide spanning this epitope mediate efficient therapy of established B16 melanoma tumours in HHDII/DP4 (p<0.0001) transgenic mouse model. Finally, we demonstrate the existence of a repertoire of responses to the citrullinated GRP78 peptide in healthy individuals (p=0.0023) with 13/17 (76%) individuals showing a response to this peptide. We propose that citrullinated GRP78 is a candidate tumour antigen and vaccination against citrullinated GRP78 may provide a promising tumour therapy approach.